Evaluation of the role of transhepatic flow in postoperative outcomes following major hepatectomy (THEFLOW): study protocol for a single-centre, non-interventional cohort study - Golriz, Mohammad; Murtha-Lemekhova, Anastasia; Khajeh, Elias; Ghamarnejad, Omid; Saeedi, Mohammed al; Strobel, Oliver; Hackert, Thilo; Müller, Beat P.; Schneider, Martin; Berchtold, Christoph; Tinoush, Parham; Mayer, Philipp; et al. (BMJ open, 2019)
Introduction Liver resection is the only curative treatment for primary and secondary hepatic tumours. Improvements in perioperative preparation of patients and new surgical developments have made complex liver resections possible. However, small for size and flow syndrome (SFSF) is still a challenging issue, rendering patients inoperable and causing postoperative morbidity and mortality. Although the role of transhepatic flow in the postoperative outcome has been shown in small partial liver transplantation and experimental studies of SFSF, this has never been studied in the clinical setting following liver resection. The aim of this study is to systematically evaluate transhepatic flow changes following major liver resection and its correlation with postoperative outcomes. - Methods and analysis The TransHEpatic FLOW (THEFLOW) study is a single-centre, non-interventional cohort study, and aims to enrol 50 patients undergoing major hepatectomy (defined as hemihepatectomy or extended hepatectomy based on the Brisbane classification) with or without prior chemotherapy. The portal venous flow, hepatic artery flow and portal venous pressure are measured before and after each resection. All patients are followed-up for 3 months after the operation. During each evaluation, standard clinical data, posthepatectomy liver failure and overall morbidity and mortality will be recorded. THEFLOW study was initiated on 25 March 2018 and is expected to progress for 2 years. - Ethics and dissemination This protocol study received approval from the Ethics Committee of the University of Heidelberg (registration number: S576/2017). The results of this study will be published in a peer-reviewed journal, and will also be presented at medical meetings. - Trial registration number NCT03762876.